Recordação e Interiorização do Conteúdo Musical - Silva, Kaique Aparecido Gonçalves e (2023)
This dissertation aims to analyze the phenomena of interiorization (Innewerden) and memory (Erinnerung) of music, based on the texts of G.W. F. Hegel, particularly in the second chapter: The Music, which is in the text Vorlesungen über die Ästhetik - Aesthetics Courses. We aim to investigate how the concepts of memory and interiorization can explain the making of music as art. Therefore, as a hypothesis, we question whether the content – Gehalt – would be placed only as an idea or if it would also be a form of access to consciousness. Indeed, our first hypothesis checked the possibilities that theoretical musical content has to create access to a memory and a feeling. Our second hypothesis faced some barriers that allowed us to understand how the content – Inhalt – presents itself to the movement that performs the interiorization. We also conclude that the dialectic of music can explain the differences between the phenomenon of interiorization of what is presented to consciousness, in this case, music as the perception of the senses.